2022
DOI: 10.1007/s00787-021-01931-2
|View full text |Cite
|
Sign up to set email alerts
|

Sleep disturbances in ADHD: investigating the contribution of polygenic liability for ADHD and sleep-related phenotypes

Abstract: Sleep disturbances are common in attention deficit hyperactivity disorder (ADHD) and associated with poor outcomes. We tested whether, in children with ADHD, (1) polygenic liability for sleep phenotypes is over- or under-transmitted from parents, (2) this liability is linked to comorbid sleep disturbances, and (3) ADHD genetic risk is associated with comorbid sleep disturbances. We derived polygenic scores (PGS) for insomnia, chronotype, sleep duration, and ADHD, in 758 children (5–18 years old) diagnosed with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 53 publications
0
8
0
Order By: Relevance
“…Systematic reviews indicate that the prevalence of ADHD in children is around 5% (Sayal, Prasad, Daley, Ford, & Coghill, 2018 ) and is characterized by attention difficulties, impulsivity and/or hyperactivity (American Psychiatric Association, 2013 ). The aetiology of ADHD is multifactorial and includes both genetic and environmental factors (Banerjee, Middleton, & Faraone, 2007 ; Faraone et al., 2005 ; Lewis et al., 2022 ). One manifestation of this aetiology is disturbed sleep, and there has been a dramatic increase in new research to better understand the association between sleep and ADHD (Weiss, Craig, Davies, Schibuk, & Stein, 2015 ).…”
Section: Introductionmentioning
confidence: 99%
“…Systematic reviews indicate that the prevalence of ADHD in children is around 5% (Sayal, Prasad, Daley, Ford, & Coghill, 2018 ) and is characterized by attention difficulties, impulsivity and/or hyperactivity (American Psychiatric Association, 2013 ). The aetiology of ADHD is multifactorial and includes both genetic and environmental factors (Banerjee, Middleton, & Faraone, 2007 ; Faraone et al., 2005 ; Lewis et al., 2022 ). One manifestation of this aetiology is disturbed sleep, and there has been a dramatic increase in new research to better understand the association between sleep and ADHD (Weiss, Craig, Davies, Schibuk, & Stein, 2015 ).…”
Section: Introductionmentioning
confidence: 99%
“…Further, the relationship between polygenic risk for ADHD and ADHD symptoms in children may be moderated by children’s sleep duration [ 56 ]. However, a recent study reported that children with ADHD do not over-inherit polygenic liability for insomnia or later chronotype [ 13 ]; however, as such studies account only for the effects of common genetic variants, the transmitted effects of rare but highly penetrant variants must also be considered. Potential pathways that may link shared genetic liability between sleep problems and ADHD symptoms in both parents and children might include dopaminergic pathways in the pre-frontal cotex, neuroinflammation and iron homeostasis [ 5 ].…”
Section: Discussionmentioning
confidence: 99%
“…These overlapping facets may be the products of complex multifactorial and bidirectional relationships between sleep problems and ADHD symptoms [ 10 , 11 ]. Further, as ADHD is highly heritable [ 2 ], and polygenic risk for ADHD and sleep problems overlap [ 12 ], there is the possibility that parents and children share overlapping genetic liability for ADHD and sleep problems (but see Lewis et al [ 13 ] who do not report increased transmitted genetic liability for insomnia or chronotype).…”
Section: Introductionmentioning
confidence: 99%
“…However, a previous study based on the polygenic transmission disequilibrium test in two samples of complete trios of ADHD probands and both biological parents observed no evidence of differential transmission of polygenic liability for insomnia. 12 In both the analyzed samples of European origin-one used as discovery (328 trios from Wales) and another considered as replication (844 trios from the IMAGE study) -even though the insomnia polygenic score suggested a risk increase, it was not significantly associated with ADHD. Differences on PRS calculation and the sample's origin might explain the difference between our results and the previously published findings.…”
Section: Discussionmentioning
confidence: 99%